2020
DOI: 10.3390/w12020427
|View full text |Cite
|
Sign up to set email alerts
|

Flooding of Piazza San Marco (Venice): Physical Model Tests to Evaluate the Overtopping Discharge

Abstract: This paper aims at evaluating the wave overtopping discharge over the pavement of “Piazza S. Marco” (Venice) in order to select the best option to mitigate the risk of flooding of the Piazza and to protect the monuments and historic buildings, e.g., the “Basilica S. Marco”. In fact, the MO.S.E. (MOdulo Sperimentale Elettromeccanico) system is designed to keep the water level below a certain value, for the safety of the lagoon, but it does not guarantee the defence of the Piazza, where flooding is still possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The hydrodynamics of the lagoon is affected by several factors, such as meteorological conditions (e.g., wind waves), fluvial inflows, and variations in tidal levels [38]. To assess the performance of WASI on the PlanetScope data, two extreme events are considered: (i) the COVID-19 lockdown in spring 2020, and (ii) a sequence of floods occurred in mid-November 2019 -unprecedented since 1969 -which were driven by a combination of extreme high tides, severe storms, and inland water inflows [39]. For the former event, we have analyzed three images acquired before (23 January, 15 and 28 February 2020) and three images captured during (19 March,8 and 13 April 2020) the COVID-19 pandemic lockdown (Figure 1a,b).…”
Section: Study Area and Datasetmentioning
confidence: 99%
“…The hydrodynamics of the lagoon is affected by several factors, such as meteorological conditions (e.g., wind waves), fluvial inflows, and variations in tidal levels [38]. To assess the performance of WASI on the PlanetScope data, two extreme events are considered: (i) the COVID-19 lockdown in spring 2020, and (ii) a sequence of floods occurred in mid-November 2019 -unprecedented since 1969 -which were driven by a combination of extreme high tides, severe storms, and inland water inflows [39]. For the former event, we have analyzed three images acquired before (23 January, 15 and 28 February 2020) and three images captured during (19 March,8 and 13 April 2020) the COVID-19 pandemic lockdown (Figure 1a,b).…”
Section: Study Area and Datasetmentioning
confidence: 99%
“…Recently, two extreme events occurred along the Venetian littoral in 2018 (Vaia storm described in [30,31]) and in 2019 ( [32,33]). The first event was characterized by an extreme significant wave height of 5.92 m and a sea level of 1.56 m relative to the local tidal reference (named ZMPS, Zero Mareografico Punta Salute), conversely, the 2019 event was characterized by an extreme sea level of 1.82 m ZMPS and a wave height of 3.5 m. Both events caused localized erosion and marine ingression along the Venetian coast.…”
Section: Case Studymentioning
confidence: 99%
“…The measured overtopping discharge for Configurations A1 and A2, relative to a cross section with vertical wall and a temporary defense barrier located at different positions, will be hereafter compared to the results presented in Ruol et al (2020) for Configuration A, that is the same cross section, in the absence of any barrier.…”
Section: Resultsmentioning
confidence: 99%
“…is closed, with reference to the local chart datum (0.23 m below m.s.l.). COASTAL ENGINEERING PROCEEDINGS 2020 Ruol et al (2020), in similar tests carried out in the absence of any mitigation measure, showed that the critical stretch of the quay is placed in proximity of the "Marciana" library. In this area, with the highest water level (1.1 m CD), almost all the tested wave states caused overtopping.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation